Nanomaterials characteristics and current utilization status in rigid pavements: mechanical features and sustainability. a review - Allujami, Hamzeh Marwan; Jassam, Taha M.; Al-Mansob, Ramez A. (2021)
Rigid pavements are recognized as one of the most widely means by which people and goods move around for popular aims and certain objectives. Nowadays, the utilization of rigid pavements is becoming an urgent demand and an increasing need, for these pavements require less maintenance and less renovation compared to other types. As a result, the structures are becoming more economical and more profitable. However, during its lifespan, normal rigid pavement is facing many challenges and difficulties. Its initial erection cost is extremely higher compared to asphalt pavements, its higher sensitivity to dynamic stresses, its higher susceptibility to temperature variations caused cracking, and further to its greater contribution to global carbon dioxide emissions. Past works of literature have been dealing with these drawbacks through employing efficient materials as alternatives to replace cement and/or aggregates in the concrete pavement mixtures. In recent years, the application of nanomaterials has received considerable interest to enhance the mechanical performance of construction materials which can also be available for rigid pavement constructions. Despite its poor performance in the fresh conditions, the addition of nanomaterials to rigid pavements has shown significant improvements in static properties like compressive and tensile strengths; dynamic properties like fatigue flexure and impact strengths. This enhancement is mainly due to the role of nanomaterials which acting as nano reinforcements and nanofillers within the concrete pavement blends. This review paper presents and discusses the behavior of nano-modified rigid pavements under different external loads. The effect of nano-SiO2, nano-CaCO3, nano-Al2O3, nano-TiO2, nano-clay and nanotubes are focused. Besides, as a promising sustainable structure, the influence of nano-SiO2 on the hardened properties of recycled rigid pavement is deeply discussed (both in normal and supplementary cementitious structures). Mechanical characteristics and optimal percentages are reviewed. A better comprehension of the characteristics of the nanostrengthening rigid pavements can provide an academic base for future works and engineering applications of developed concrete materials in the pavement construction industry.